2019
DOI: 10.1002/ptr.6566
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Baicalin relieves TNF‐α‐evoked injury in human aortic endothelial cells by up‐regulation of miR‐145

Abstract: Hypertension is recognized to be associated with low‐grade inflammation. Baicalin (BAI) is reported to possess various pharmacological including anti‐inflammatory activities. This research explored the molecular mechanism by which BAI functions in human aortic endothelial cells (HAECs). HAECs were pretreated with BAI. Cell viability, apoptosis, and expressions of crucial proteins were respectively evaluated using cell counting kit‐8 assay, flow cytometry, and western blot. Productions of cytokines were respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…[24] TNF-α treatment can significantly induced human aortic endothelial cells to release inflammatory cytokines, including IL-6 and IL-8, while reducing the expression of miR-145. [25] In this study, we found that the expression of miR-145 decreased in RHD patients, especially in TH group. Interestingly, we found that miR-145 was negatively correlated with LAD, IL-6 level, and D-D level, respectively, suggesting that miR-145 may be involved in the pathogenesis of RHD, and the significant decrease of miR-145 expression can predict intracardiac thrombosis in patients with RHD.…”
Section: Discussionmentioning
confidence: 59%
“…[24] TNF-α treatment can significantly induced human aortic endothelial cells to release inflammatory cytokines, including IL-6 and IL-8, while reducing the expression of miR-145. [25] In this study, we found that the expression of miR-145 decreased in RHD patients, especially in TH group. Interestingly, we found that miR-145 was negatively correlated with LAD, IL-6 level, and D-D level, respectively, suggesting that miR-145 may be involved in the pathogenesis of RHD, and the significant decrease of miR-145 expression can predict intracardiac thrombosis in patients with RHD.…”
Section: Discussionmentioning
confidence: 59%
“…In vivo, experimental data confirmed that baicalin forcefully lowered the blood pressure partly via decreasing the serum levels of high-sensitivity CRP, IL-6 and IL-1b in spontaneously hypertensive rats (SHRs) (Wu et al, 2019). Similarly, another vitro study showed that baicalin extenuated contents of TNF-a by altering miR-145 expression and significantly ameliorating TNF-a inflammatory injuries in human aortic endothelial cells (HAECs) (Li et al, 2020). With the popularization of the Holistic concept, numerous studies have revealed that a damage in the intestinal barrier, is considered as a critical role in the pathogenesis of hypertension primarily by exacerbating the development of chronic low-grade inflammation (Santisteban et al, 2017;Jaworska et al, 2017).…”
Section: Hypertensionmentioning
confidence: 83%
“…Geniposide protects H9c2 cells against lipopolysaccharide (LPS)-induced apoptosis and inflammation by regulating miR-145 expression and the MEK/ERK signaling pathway (9). In human aortic endothelial cells, TNF-α treatment markedly induced the release of inflammatory cytokines, including monocyte chemoattractant protein-1 (MCP-1), IL-6 and IL-8, whilst decreasing the expression of miR-145 (10). Moreover, He et al (11) demonstrated that LPS treatment markedly elevated TNF-α levels, which strongly inhibited miR-145 expression under hyperglycemic conditions.…”
Section: Introductionmentioning
confidence: 99%